2010
DOI: 10.2188/jea.je20090057
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Effort–Reward Imbalance in School Settings: A Novel Approach and Its Association With Self-Rated Health

Abstract: BackgroundWe attempted to apply the model of effort–reward imbalance (ERI) to school settings in order to measure students’ psychosocial stress and analyze its association with self-rated health in adolescents.MethodsA cross-sectional survey was conducted in Kunming, China among 1004 Chinese students (468 boys and 536 girls) in grades 7 through 12, using a 19-item effort–reward imbalance questionnaire.ResultsSatisfactory internal consistencies for the scales for effort and reward were obtained; the value for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 28 publications
3
33
0
Order By: Relevance
“…The validity of ERI-SF was assessed by testing the association between the subscale of ERI-SF and perceived health status and job strain. With regard to poor health status, there is convincing evidence of adverse health effects on ERI from previous studies (Li, Loerbroks, Shang, et al, 2012;Li, Shang, Wang, & Siegrist, 2010). The current study found significant associations between ERI and job strain, consistent with an earlier study (Tsutsumi, Kayaba, Theorell, & Siegrist, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…The validity of ERI-SF was assessed by testing the association between the subscale of ERI-SF and perceived health status and job strain. With regard to poor health status, there is convincing evidence of adverse health effects on ERI from previous studies (Li, Loerbroks, Shang, et al, 2012;Li, Shang, Wang, & Siegrist, 2010). The current study found significant associations between ERI and job strain, consistent with an earlier study (Tsutsumi, Kayaba, Theorell, & Siegrist, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…() reported in a longitudinal study that the prevalence of attention deficit/hyperactivity disorder tends to decrease with age within the 9‐ to 16‐year‐old age bracket (from 2.2 to 0.3%), whereas evidence for depressive disorder increases (from 0.5 to 3.1%). On the other hand, we found that the SRH scores were consistent in the fifth and eighth graders across gender and were higher in eighth‐grade boys than in eighth‐grade girls; this is consistent with previous reports (Breidablik et al ., ; Li et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Self-rated health was used in some epidemiological studies as an indicator of both health outcomes and health-related quality of life (Zullig et al, 2005). Lifestyle, school-related stress, and environments have been found to affect SRH ratings among adolescents (Karademas et al, 2008;Li et al, 2010). Self-rated health was also a predictor of problematic behaviors in areas such as educational attainment (Haas & Fosse, 2008;Jackson, 2009), bullying (Gobina et al, 2008), and alcohol and tobacco habits (Johnson & Richter, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Stress scales are usually validated by showing a strong association between the stress index and self-rated health (Li et al, 2010;Niedhammer et al, 2004;Siegrist et al, 2008). The explanatory power of the SSS has also been examined for subjective health status.…”
Section: Criterion Validitymentioning
confidence: 99%